O flow e a recomendação do produto por meio de tecnologias digitais com realidade aumentada no setor do varejo digital - Dornelles, Luis Antonio Lampert (Universidade do Vale do Rio dos Sinos, 2025)
The possibility of experiencing a product in a virtual and customizable way grants AR tools the status of a strategic resource, creating immersive and interactive experiences. Companies aware of this impact increasingly invest in different ways to reach their target audience. In this context, this study aims to analyze changes in consumer behavior regarding product recommendation after the shopping experience. For this purpose, a survey was conducted to collect respondents' impressions following a simulated purchase of Ray-Ban glasses. . The sample was selected through non-probabilistic convenience sampling. To facilitate data collection, no specific respondent profile was required for interacting with the website or completing the questionnaire. The study population consisted of consumers aged between 15 and 67 years, located in Porto Alegre/RS and its metropolitan area. This group encompasses a broad diversity in terms of age, experience, and familiarity with AR-based shopping websites, totaling 245 respondents. A theoretical model was developed to identify the influence of flow in moderating the relationships established between interaction, engagement, and behavioral response – word of mouth. Structural Equation Modeling (SEM) was used as the analysis method to assess whether the customer's level of immersion altered these relationships. Through SEM, a positive relationship was confirmed between product vividness, user engagement, and interactivity, as well as their influence on product recommendation. On the other hand, the relationship between the need for touch (NFT), engagement, and interactivity, as well as flow moderation in these relationships, could not be confirmed. Despite the identified limitations, the results suggest that improving product vividness, along with the development of an intuitive and easy-to-use tool, enhances the user experience and helps maintain their motivation during the virtual shopping_journey.
Keywords: Realidade Aumentada (AR); Flow; Nitidez; Necessidade de toque; Interação; Engajamento; Recomendação do produto; Augmented Reality (AR); Vividness; Need for touch; Interaction; Engagement; Product recommendation; ACCNPQ::Ciências Sociais Aplicadas::Administração